Abusive Supervision: A Meta-Analysis and Empirical Review. (July 2017) - Mackey, Jeremy D.; Frieder, Rachel E.; Brees, Jeremy R.; Martinko, Mark J.
We conducted a meta-analysis and empirical review of abusive supervision research in order to derive meta-analytic population estimates for the relationships between perceptions of abusive supervision and numerous demographic, justice, individual difference, leadership, and outcome variables. The use of psychometric correction enabled us to provide weighted mean correlations and population correlation estimates that accounted for attenuation due to measurement error and sampling error variance. Also, we conducted sensitivity analyses that removed the effects of large samples from analyses. Then, we conducted subgroup analyses using samples drawn from the United States to provide population correlation estimates that corrected for attenuation due to measurement error, sampling error variance, and indirect range restriction. Finally, we examined measurement artifacts resulting from various adaptations of Tepper's abusive supervision measure. The results reveal that although the associations between perceptions of abusive supervision and outcome variables appear to be universally negative, the magnitude of the relationships between perceptions of abusive supervision and antecedent and outcome variables varies according to the design features of studies. Contributions to theory and practice, strengths and limitations, and directions for future research are discussed.